Trust, agreements, and occasional breakdowns: Veterinarians' perspectives on farmer-veterinarian relationships and use of antimicrobials for Swedish dairy cattle - Hedvig Gröndal; Isabel Blanco-Penedo; Nils Fall; Susanna Sternberg-Lewerin (Journal of Dairy Science, 2023)
ABSTRACT: Studies have shown that farmer-veterinarian relationships influence antimicrobial use (AMU) in livestock, though how they do so is unclear. On the one hand, research shows that well-established veterinarian-farmer relationships are positive for implementation of antibiotic stewardship and restrictive AMU. On the other hand, studies also show that farmer demands can increase antimicrobial prescribing and that prescribing antimicrobials can strengthen the veterinarian's relationship with farmer clients. In the present study, we focus on veterinarians' perspectives on the relationships between dairy cattle farmers and veterinarians in Sweden and explore what characterizes these relationships when restrictive AMU is described as unproblematic and when AMU becomes a matter of tension or conflict. The study draws on semistructured interviews with 21 veterinarians working with livestock in Sweden. Interviews were analyzed thematically. The study shows that from the perspectives of veterinarians, well-established veterinarian-farmer relationships generally facilitate restrictive AMU in 3 slightly different but related ways: (1) they create trust in the veterinarian and their prescribing decisions; (2) they create shared understanding concerning when antimicrobials are needed and not needed; and (3) they facilitate constructive discussions between veterinarians and farmers on AMU. To make the farmer feel listened to and to come to an agreement on AMU was described as central for the veterinarians. However, the veterinarians described agreements on restrictive AMU as sometimes requiring strategic work, such as discussions to motivate the farmer and leave the door open for antimicrobials later if needed. Such work takes time and energy and is easier within well-established relationships according to the veterinarians. We also identified examples where veterinarians explained that they occasionally make compromises with farmers concerning antimicrobials—compromises that, according to the veterinarians, facilitate the relationship with the farmer, which in turn facilities restrictive AMU in the longer term. The examples in our interviews where antimicrobials became a matter of tension and even conflict between veterinarians and farmers could, with a few exceptions, be traced to absence of well-established relationships. However, some veterinarians also described AMU as a matter of tension within well-established relationships, especially with older farmers who do not trust new treatment strategies. We also found a small number of examples where disagreements on antimicrobials made a relationship with specific farmers impossible. Thus, even though the interviewed veterinarians generally meant that their restrictive antimicrobial prescribing did not threaten the relationship with the farmer, our study also, to some extent, confirms research showing that restrictive AMU can harm the relationship with some clients who simply choose another, less restrictive, veterinarian. In summary, our study supports that decisions on AMU cannot be reduced to the individual prescriber's behavior, nor to a strict medical judgment. Antimicrobial use for dairy cattle needs to be understood as taking form in relationships in which both veterinarians and farmers are active parts.